SPORT FUND RAISING - Miodrag Koprivica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Fund raising represent comlex of measurements and activities on assets gathering for exact collective demands. Sport in some parts its own needs and selfaffirmation satisfy oneself on the market, but various categories of sports and social groups can't contest on the market, that is fundraising role. That activity ask good menagment preparation, sharp planning and great public involvment. All rules of the modern business are the very same for the fund raising.